Effectiveness of ginger extract (Zingiber officinale Rosc.) on catfish (Clarias gariepinus) infected by Aeromonas hydrophila - Riztawati, Nurika Alawyah; Lumbessy, Salnida Yuniarti; Setyowati, Dewi Nuraeni (Acta Aquatica: Aquatic Sciences Journal, 2023)
Research on the effectiveness of ginger extract (Zingiber officinale Rosc.) against catfish (Clarias gariepinus) infected with Aeromonas hydrophila bacteria aims to analyze the antibacterial effectiveness of ginger extract against catfish injected with A. hydrophilla bacteria and to analyze the optimum dose of ginger extract as an immunostimulant in control of A. hydrophila infection. This research was carried out on January 26, 2021 to February 26, 2021 for 30 days and took place at the Microbiology Laboratory of the Faculty of Agriculture, the Laboratory of the Faculty of Mathematics and Natural Sciences and the Wet Laboratory of the Aquaculture Study Program, Faculty of Agriculture, University of Mataram. The method used in this study is an experimental method with a completely randomized design (CRD). The treatments were P1 (control), P2 (extract dose 30 ppm), P3 (extract dose 60 ppm) and P4 (extract dose 90 ppm). The ginger extract dose of 90 ppm (P4) was the optimum dose in the results of this study because it could give the best results on all the parameters measured. Keywords : Aeromonas hydrophila, , ginger extract. catfish